Unveiling per- and polyfluoroalkyl substance contamination in Chinese paper products and assessing their exposure risk - Yan-Fei Chen; Ting Liu; Li-Xin Hu; Chang-Er Chen; Bin Yang; Guang-Guo Ying (Environment International, 2024)
The contamination characteristics, migration patterns and health risks of per- and polyfluoroalkyl substances (PFAS) were investigated in 66 Chinese paper products by using target and non-target screening methods. Among 57 target PFASs, 5 and 6 PFASs were found in the hygiene paper products (<LOQ-12.6 ng/g) and stationery paper products (<LOQ-8.8 ng/g), respectively. A total of 25 PFASs were detected in the 39 food contact paper products, with the highest concentration of 1630 ng/g. Suspect and non-target analysis have found 28 PFASs with confidence levels 1–3, 132 certain PFAS compounds (level 4) and 56 homologue groups (level 5), containing newly identified long-chain polyfluorocarboxylic acid (9:3/11:3FTCA, 11:3/13:3FTUCA) and X:2 FTOH-Sulfate. A potential transformation relationship between the detected PFAS was proposed, starting from X:2 FTOH and finally transforming to CnF2n+1COOH. Microwave heating can increase the release of PFAS in popcorn bags and convert long-chain PFAS into short-chain ones. The migration experiments indicated that the ethanol in food simulants can increase the migration of PFAS, and short-chain PFAS exhibits a greater migration trend. The estimated daily intake (EDI) values for 6 of 18 paper bowls/plates exceeded the recommendation of 0.63 ng/kg bw/day by the European Food Safety Authority (EFSA), posing a potential threat to human health.